Ideal free distribution of Daphnia under predation risk—model predictions and experimental verification. (3rd July 2018) - Maszczyk, Piotr; Babkiewicz, Ewa; Czarnocka-Cieciura, Marta; Gliwicz, Z Maciej; Uchmański, Janusz; Urban, Paulina
Abstract: The vertical distribution of planktonic animals, such as Daphnia, in overlapping gradients of food concentration and risk of visual predation should depend on Daphnia population density and should be the result of the group effect of optimizing decisions taken by each individual (juvenile or adult), trading-off a high growth rate to low mortality risk. We tested this hypothesis by comparing the theoretical distributions from simulations based on an experimentally parameterized, optimizing individual-based model (consistent with the assumptions of the concept of the interference ideal free distribution with costs) with distributions observed in laboratory experiments. The simulations were generated for two scenarios, where the shape of the functional response of fish is consistent with either type II or III. The results confirmed the hypothesis. The greatest similarity of the distributions obtained in the experiments and simulations was found for the simulations based on the scenario assuming the type III rather than type II for both age classes of Daphnia . This was consistent with the results of the experiments for the model parameterization, which revealed the type III functional response of fish. Therefore, the results suggest that aggregating may be maladaptive as an anti-vertebrate-predation defense in the case of zooplankton.